2005
DOI: 10.1083/jcb.200412071
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5 phosphorylation of huntingtin reduces its cleavage by caspases

Abstract: Huntington's disease (HD) is a neurodegenerative disorder caused by an expanded polyglutamine (polyQ) tract in the huntingtin (htt) protein. Mutant htt toxicity is exposed after htt cleavage by caspases and other proteases release NH2-terminal fragments containing the polyQ expansion. Here, we show htt interacts and colocalizes with cdk5 in cellular membrane fractions. Cdk5 phosphorylates htt at Ser434, and this phosphorylation reduces caspase-mediated htt cleavage at residue 513. Reduced mutant htt cleavage r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
155
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(158 citation statements)
references
References 31 publications
3
155
0
Order By: Relevance
“…Our studies found that phosphorylation at Ser-514 of the androgen receptor, a site distal to the caspase cleavage site at amino acid 154, enhanced cellular toxicity and the production of cytotoxic fragments. Recent work on Htt suggests that CDK5-mediated phosphorylation of Ser-434 reduces cleavage of Htt at a distal caspase-3 cleavage site (amino acid 513) (39). A key role for phosphorylation of Ser-776 of ataxin-1 was shown to trigger toxicity in SCA1 in vivo (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Our studies found that phosphorylation at Ser-514 of the androgen receptor, a site distal to the caspase cleavage site at amino acid 154, enhanced cellular toxicity and the production of cytotoxic fragments. Recent work on Htt suggests that CDK5-mediated phosphorylation of Ser-434 reduces cleavage of Htt at a distal caspase-3 cleavage site (amino acid 513) (39). A key role for phosphorylation of Ser-776 of ataxin-1 was shown to trigger toxicity in SCA1 in vivo (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation at various serine residues prevents cleavage of mutant huntingtin into more toxic fragments, decreases neural cell death in vitro (5)(6)(7)(8)(9)(10), and/or restores Htt functions that are compromised by the mutation (8,11). The most dramatic effects have been described for huntingtin phosphorylation at serine 13 and serine 16.…”
mentioning
confidence: 87%
“…The kinase activity of Cdk5 is required for suppression of mhtt inclusion body formation It was previously reported that Cdk5 physically binds htt (Luo et al, 2005). To examine this molecular interaction, we examined coimmunoprecipitation of mhtt with anti-Cdk5 or anti-p35 antibody, or of Cdk5 or p35 with anti-GFP antibody, but we could not detect binding of either Cdk5 or p35 to any tNhtt-poly(Q)-EGFP proteins under our experimental conditions (data not shown).…”
Section: Suppression Of Mhtt Aggregate Formation By Cdk5/p35mentioning
confidence: 97%
“…We used the N-terminal exon 1 fragment of huntingtin (tNhtt) including the poly(Q) stretch in the middle, which is much shorter than those used previously by Luo et al (2005) and Anne et al (2007). The effect of Cdk5/p35 on tNhtt aggregate formation was examined by transient expression in COS-7 cells, frequently used for studies on mhtt aggregation (Onodera et al, 1997;Hazeki et al, 1999).…”
Section: Suppression Of Mhtt Aggregate Formation By Cdk5/p35mentioning
confidence: 99%
See 1 more Smart Citation